Predatory vs Legitimate Publishing And Its Consequences: A Review - Shrestha, Jiban; Timsina, Krishna Prasad; Subedi, Sudeep (Qualitative and Quantitative Methods in Libraries, 2021)
Predatory journals are a global threat. They accept articles for publication without any form of an editorial or peer review process. Predatory publishing is just a  wastage of time, money, resources, and efforts. Predatory publishers take publication fees from authors and publish articles easily and quickly even in a week or a couple of days. On the contrary, publishing in a legitimate journal is a difficult task, that demands high-quality research, a lot of time in addressing the reviewers’ comments, and thus months or even years in some instances for a paper to be published. Publication of research works in legitimate journals is important for researchers for enhancing their careers and reputation. Publication in a predatory journal creates a negative reputation, therefore such publications should be avoided. The authors should be encouraged to publish their works in legitimate journals which are registered in or member of the World Association of Medical Editors (WAME), Directory of Open Access Journals (DOAJ), Open Access Scholarly Publishers Association (OASPA), International Association of Scientific, Technical & Medical Publishers (STM) and  Committee on Publication Ethics (COPE). The universities, research organizations, and funding agencies should make joint efforts to promote only those journals which are indexed  in Web of Science, Scopus  PsycINFO, and other authentic databases.